2017
DOI: 10.1192/bjp.bp.116.194019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of childhood trauma on diagnosis and substance use in first-episode psychosis

Abstract: BackgroundChildhood trauma has been significantly associated with first-episode psychosis, affective dysfunction and substance use.AimsTo test whether people with first-episode psychosis who had experienced childhood trauma, when compared with those who had not, showed a higher rate of affective psychosis and an increased lifetime rate of substance use.MethodThe sample comprised 345 participants with first-episode psychosis (58% male, mean age 29.8 years, s.d.=9.7).ResultsSevere sexual abuse was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…While the selfmedication hypothesis has some intuitive appeal, the available data do not provide evidence to support this as a causal explanation for the use of alcohol/substances in patients with schizophrenia (Buchanan, Strauss, Breier, Kirkpatrick, & Carpenter, 1997;Cantwell et al, 1999;Hambrecht & Hafner, 1996;Kovasznay et al, 1997;Linszen et al, 1994;Lysaker, Bell, Beam-Goulet, & Milstein, 1994). Substance use, actually, tends to be less common in patients with primarily negative symptoms, and even first episode patients, including those not treated with antipsychotic medications, frequently use substances (Batki, Leontieva, Dimmock, & Ploutz-Snyder, 2008;Brunette et al, 2017;Buchanan et al, 1997;Tomassi et al, 2017).…”
Section: Basis Of Substance Use Disorder In Schizophreniamentioning
confidence: 98%
“…While the selfmedication hypothesis has some intuitive appeal, the available data do not provide evidence to support this as a causal explanation for the use of alcohol/substances in patients with schizophrenia (Buchanan, Strauss, Breier, Kirkpatrick, & Carpenter, 1997;Cantwell et al, 1999;Hambrecht & Hafner, 1996;Kovasznay et al, 1997;Linszen et al, 1994;Lysaker, Bell, Beam-Goulet, & Milstein, 1994). Substance use, actually, tends to be less common in patients with primarily negative symptoms, and even first episode patients, including those not treated with antipsychotic medications, frequently use substances (Batki, Leontieva, Dimmock, & Ploutz-Snyder, 2008;Brunette et al, 2017;Buchanan et al, 1997;Tomassi et al, 2017).…”
Section: Basis Of Substance Use Disorder In Schizophreniamentioning
confidence: 98%
“…An earlier onset of heroin use is associated with poorer outcomes, including more rapid progression from heroin use to dependence (Chen et al 2009, Woodcock et al 2015), and a longer heroin use career (Best et al 2008). Childhood trauma and maltreatment have been found to be strongly associated with an earlier onset of heroin use and dependence (Khoury et al 2010, Li et al 2012, Tomassi et al 2017). More recent birth cohorts have higher rates of psychiatric comorbidity such as depression (Mills et al 2004) and report more rapid transitions from first heroin use, to regular use and treatment-seeking compared to older birth cohorts (Kessler et al 2001, Kessler et al 2001, Mills et al 2004, Woodcock et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 23 articles selected for review, 19 (83%) directly analysed the association between the two environmental risk factors for psychosis: childhood trauma and substance use. In 16 of them, a positive association was found between both factors: specifically, in nine studies, childhood trauma was related to the use of different substances (Conus et al, 2010;Cutajar et al, 2010;Haahr et al, 2018;Neria, Bromet, Sievers, Lavelle, & Fochtmann, 2002;Rosenberg, Lu, Mueser, Jankowski, & Cournos, 2007;Schalinski, Fischer, & Rockstroh, 2015;Scheller-Gilkey, Moynes, Cooper, Kant, & Miller, 2004;Tomassi et al, 2017;van Nierop et al, 2016); in five studies, childhood trauma was related to cannabis use (Ajnakina et al, 2018;Compton, Furman, & Kaslow, 2004;Harley et al, 2010;Ramsay, Flanagan, Gantt, Broussard, & Compton, 2011;Saddichha, Werker, Schuetz, & Krausz, 2015); one study based its analyses on the relationship between trauma and cocaine use (Banducci, Hoffman, Lejuez, & Koenen, 2014); and another investigated the relationship between trauma and methamphetamine use (Ding, Lin, Zhou, Yan, & He, 2014). The remaining three studies found no significant relationship.…”
Section: Relationship Between Childhood Trauma and Substance Usementioning
confidence: 99%
“…In one of these studies, major methodological flaws were found for the selection and comparability assessment (Schalinski et al, 2015). Three other studies related sexual abuse in childhood with a higher probability of presenting a diagnosis of SSD (Ding et al, 2014;Houston et al, 2011;Tomassi et al, 2017). Barrigon et al (2015) and Harley et al (2010) found that the chances of suffering psychosis were 7.3 and 5.2 times higher, respectively, for those who had suffered childhood trauma than for those who had not experienced it, and both works had moderate methodological quality.…”
Section: Relationship Between Childhood Trauma and Ssdmentioning
confidence: 99%